Multi-scenario simulation of land use optimization based on ecosystem services and ecological security patterns in the Liaohe River Basin - Luo, Qing; Zhang, Jing; Bao, Yajing; Zhang, Yilin; Yu, Jie; Li, Jiaxin; Wu, Xunwen; Zhang, Shuai; Cao, Nan; Wang, Dongli (Frontiers in Environmental Science, 2025)
IntroductionUnder the combined pressures of global climate change and intensive land use, regional ecosystem services face escalating risks of degradation and spatial imbalance. Understanding the complex interactions among ecosystem services and identifying their spatial drivers are critical for developing adaptive land use strategies and improving ecological security, particularly in ecologically sensitive basins like the Liaohe River Basin (LRB).MethodsTherefore, this study proposed an integrated framework combining the InVEST model, Geographical Detector, and PLUS model to evaluate ecological service dynamics and optimize spatial governance in the LRB. Based on five key ecosystem services (carbon storage, food production, habitat quality, soil retention, and water yield) from 2000 to 2020 and their synergy–tradeoff relationships, we identified three levels of ecological security patterns (ESPs). These ESPs were further embedded as redline constraints in scenario-based land use simulations under four development pathways, forming a spatial structure that links ecological function with landscape connectivity and couples service assessments with spatial policy optimization.ResultsThe results showed that: (1) the Total Ecosystem Service (TES) exhibited a spatial gradient of high values in the east and west and low values in the central basin, with the strongest synergy with habitat quality, and the weakest with water yield; (2) ecosystem service bundle zoning revealed that the Comprehensive Service Function Zone and the Ecological Buffer Zone had the highest levels of diversity and connectivity, while the Agricultural Development Priority Zone exhibited a strong coupling between spatial structure and dominant function; (3) among different scenarios, the ecological-priority scenario (PEP) reduced net forest loss by 63.2% compared to the economic-priority scenario (PUD), significantly enhancing ecological spatial integrity.DiscussionThis study proposed a scenario-based simulation framework to support ecological redline delineation and watershed-scale ecosystem governance for territorial ecological restoration.